2018
DOI: 10.4067/s0034-98872018000901033
|View full text |Cite
|
Sign up to set email alerts
|

Utilidad de la crio-tecnología para uso diagnóstico y terapéutico en neumología intervencionista: crio-biopsia pulmonar transbronquial y crioterapia

Abstract: Transbronchial cryobiopsies and cryotherapy in lung diseases Bronchoscopy cryoprobes are used for palliative treatment of endobronchial obstructions caused by tumors and removal of granulation tissue or foreign bodies. Currently this technology is also used for diagnosis of diffuse interstitial lung disease (ILD). The multidisciplinary team that establishes the clinical, radiological and histopathological correlation in ILD, decides about performing a surgical lung biopsy when the characteristics of the inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…According to Montufar et al [27] and Troy et al [28], TBLC is suggested as a method of choice compared with SLB, which remains the gold standard, especially when applied in the context of MDD. On the other hand, the lack of a standard technique for TBLC has led Lynch et al [14] to consider SLB as a histologic tool for ILD diagnosis.…”
Section: Mdd Has a Crucial Role In Guiding The Choice Of Lung Tissue ...mentioning
confidence: 99%
“…According to Montufar et al [27] and Troy et al [28], TBLC is suggested as a method of choice compared with SLB, which remains the gold standard, especially when applied in the context of MDD. On the other hand, the lack of a standard technique for TBLC has led Lynch et al [14] to consider SLB as a histologic tool for ILD diagnosis.…”
Section: Mdd Has a Crucial Role In Guiding The Choice Of Lung Tissue ...mentioning
confidence: 99%